Imaging of Renal Angiomyolipomatosis (Journal of Renal and Hepatic Disorders, 2018)
Angiomyolipoma is a type of benign renal tumor. It is sporadic and isolated in 80% of cases. The remaining 20% is associated with tuberous sclerosis complex or pulmonary lymphangioleiomyomatosis. Generally, angiomyolipomas manifest themselves as angiomyolipomatosis, in which the angiomyolipomas are larger, bilateral, and widespread. Understanding whether angiomyolipomas are present in the context of angiomyolipomatosis is of considerable importance because it might be associated with malignant lesions. This article provides an overview of the radiological features of renal angiomyolipomatosis under different imaging techniques such as ultrasound, computed tomography, and magnetic resonance.
Keywords: angiomyolipoma; lymphangioleiomyomatosis; PEComa; renal angiomyolipomatosis; tuberous sclerosis